Numerical study on inter-particle effects for multiple reacting biomass and coal particles based on Micro-CT morphology - Dongyu Liang (Heliyon)
Co-firing of biomass with coal combines the environmental benefits of renewable biomass with the high energy content of coal. Although the common numerical simulation treats the biomass and coal particles with ideal morphology, real particles often demonstrate nonsmoothed surface and irregular shape. To understand the impact of particle morphology in a group of biomass and coal particles co-firing together and to inform simple models appropriate, this study investigated the interparticle effects among particles using realistic particle morphology, focusing on fluid dynamics such as temperature distribution, flow patterns and drag coefficients. Particle-scale computational fluid dynamics (CFD) simulations using micro-CT imaging showed that realistic particle shapes resulted in nonuniform flow fields and temperature distributions with different reaction intensities due to the species transportation. It is in contrast to traditional ideal shape models, which often rely on simplified spherical representations of particles and cannot capture the intricacies of real particle shapes. Realistic models revealed more complex surfaces, highly irregular particle structures, and varied reaction zones that affected the overall dynamics. In addition, changing the orientation of one particle affects the combustion characteristics of neighboring particles. This effect is also not captured while using the spherical structure. These differences underscore the critical impact of particle morphology on drag and heat transfer, thereby challenging conventional spherical models. The findings of this study advocate for a paradigm shift in CFD modeling approaches, emphasizing the importance of realistic particle representation to improve the accuracy of predictions and enhance the co-firing system efficiency.